Propriedades psicométricas do teste de Pfister: versão tradicional e informatizada - Perissinotto, Rodrigo (2024)
With the aim of contributing to the development of a computerized version of the Pfister Colored Pyramids Test (CPT-i), this thesis proposed to synthesize the psychometric properties of the test in its traditional version, investigate the equivalence between the two forms of application and verify validity evidence for some TPC-i scores. Thus, three studies were developed, one theoretical and two empirical. The theoretical study aimed to synthesize the psychometric properties of the Pfister Colored Pyramids Test through a systematic review of the literature. 37 articles were retrieved, in which it was observed for each CPT variable which presented reliability studies, validity evidence and standards. Robust evidence of reliability was identified for specific variables, such as formal appearance and chromatic formula. Furthermore, the article highlights significant relationships between CPT variables and intellectual and emotional development factors, providing norms for different age groups. With regard to empirical studies, 585 protocols were collected with participants from different regions of the country aged between 18 and 74 years, who reported not having a psychopathological diagnosis. All protocols were coded by researchers with training and experience in using the instrument. For reliability studies, 115 protocols were sent to independent judges and the intraclass correlation coefficient (ICC) was calculated for the variables placement mode (considering vertical and horizontal orientation separately), formal appearance and chromatic formula. Good reliability was observed for the placement mode variables (95%CI = 0.79-0.91). Excellent reliability for the variables formal appearance (95%CI = 0.88-0.94) and chromatic formula (95%CI = 0.994 to 0.997). For the equivalence study, the 585 protocols collected in a computerized way were compared with 288 protocols from the bank that constituted the current normative parameters of the CPT. Equivalence was measured using two one-sided tests (TOST) to verify the equivalence of scalar variables and TOST of two proportions for categorical variables. The results indicated equivalence for most variables and low effects for non-equivalent ones. Which suggests equivalence between the versions. To study evidence of validity of the TPC-i, a subsample of 371 people, participants from the Midwest who took the computerized group test, were invited to answer the Personality Inventory for DSM-5 (PID-5). Next, a multinomial regression analysis was carried out and an association was found between the colors, chromatic syndromes and switching behavior of the CPT-i and several facets of the PID-5. Such results point to evidence of convergent validity between the instruments, corroborating different interpretations attributed to the CPT scores, as well as suggesting a new variable, switching behavior. Finally, taken together, these studies ix confirm the robustness of the CPT as a valid and reliable psychometric tool, both in its traditional and computerized formats, and expand the possibilities of its application and interpretation in the psychological context.